Building sustainable relationships: Service innovation at the pinnacle of touristic achievement - Cheng, Boon Liat *; Mansori, Shaheen; Cham, Tat Huei; Dent, Michael M *; Yusman, Y. (MAG Scholar, 2021)
Asia Pacific is renowned as a travelling hot spot amongst both domestic and international tourists. With Malaysia as the focal point, and based on the foundation of Stimulus-Organism-Response (SOR), this study aims to explore different routes undertaken by tourists towards both satisfaction and loyalty concerning the Malaysian tourism industry, following the impacts of service innovation and destination image. A self-administrated survey was conducted across 322 tourists. The significance of the hypothesized relationships was further tested by employing the AMOS’s structural modelling approach. Obtained results demonstrate that service innovation as a direct antecedent to destination loyalty, destination image and tourist satisfaction. Destination image also has a direct influence on destination loyalty. The mediating roles of destination image and tourist satisfaction between service innovation and destination loyalty were also established. The findings determined service delivery and innovation as more effective marketing tools to tourism practitioners for building brand reputation and tourists’ loyalty. Service innovation remains absolutely crucial in the competitive tourism marketplace to build and sustain tourist satisfaction and destination loyalty.